LIVING WITH ALBINISM IN SOUTH AFRICA: UNCOVERING THE HEALTH CHALLENGES FROM A LEGAL PERSPECTIVE - MM Mswela (Obiter, 2022)
The Cancer Association of South Africa (CANSA) has acknowledged that persons with albinism face the highest risk of developing skin cancer. While information concerning their susceptibility to cancer is very important, CANSA observed that such information is communicated to persons with albinism at a very late stage, especially those living in rural areas of South Africa. The Albinism Society of South Africa has revealed that the national health system has failed to adequately consider and take into account the health care needs of persons living with albinism. Very few persons with albinism have access to sunglasses with a high UV protection screen to relieve light sensitivity, or to preventative services such as dermatological skin checks, eye checks and eye corrections. This article establishes that the specialised health intervention required by persons with albinism is not prioritised in South Africa’s health care plan. The author argues that a well-timed intervention into the health needs of persons with albinism will have a penetrative influence on the fate of a small yet significant population. The recognition of the right of access to health care in the South African Constitution affords persons living with albinism the right to challenge the government’s failure to provide them with essential health care services and health accessories. This article also discusses the pertinent clinical aspects of albinism, with the aim of contextualising the legal discussion in the rest of the article.